2019
DOI: 10.1101/653063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary forces on different flavors of intrinsic disorder in the human proteome

Abstract: In this study, we perform a systematic analysis of evolutionary forces (i.e., mutational bias and natural selection) that shape the codon usage bias of human genes encoding for different structural and functional variants of proteins. Well-structured proteins are expected to be more under control by natural selection than intrinsically disordered proteins because one or few mutations (even synonymous) in the genes can result in a protein that no longer folds correctly. On the contrary, intrinsically disordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…In summary, our results corroborate our previous claim to consider IDPRs and IDPs as distinct protein variants [19,26]. At the same time, we identify IDPs as the true natively unfolded proteins, having peculiar functional and evolutionary features but also distinct physical-chemical and structural properties.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In summary, our results corroborate our previous claim to consider IDPRs and IDPs as distinct protein variants [19,26]. At the same time, we identify IDPs as the true natively unfolded proteins, having peculiar functional and evolutionary features but also distinct physical-chemical and structural properties.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, performing systematic analyses of these variants in terms of evolutionary forces acting on them, we have recently shown that IDPRs on the one side are subject to different patterns of evolutionary pressures with respect to IDPs and ORDPs on the other one [26]. protein segments with transient residual structure), inducible foldons (i.e., segments that are able to fold at interaction with specific binding partners), nonfoldons (i.e., protein segments with functions depending on their intrinsically disordered nature), and unfoldons (i.e., segments that are able to unfold under specific conditions, becoming functional) [9,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted above, P4 is predicted to be a disordered protein (Supplemental Figure 2). Many intrinsically disordered proteins evolve rapidly [75][76][77][78], and therefore, predicting a function for P4 is difficult based on amino acid sequence. Accordingly, analyses based on sequence similarity were overall minimally informative.…”
Section: P4 (Si:dkey-56 M195)mentioning
confidence: 99%